Intensive Management of Spontaneous Basal Ganglia Hemorrhage: A Case Report - Liliriawati Ananta Kahar; Rico Ikhsani; Wiwi Monika Sari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Simultaneous non-traumatic bilateral basal ganglia haemorrhage is an infrequent entity. ICH accounts for 10 to 20 % of all cerebrovascular events in the US, with 30-day mortality up to 40%. The predisposing factors and pathophysiological processes leading to simultaneous bilateral basal ganglia development are not well known. Case presentation: A 43-year-old female patient was diagnosed with spontaneous intracerebral haemorrhage in the left basal ganglia and intraventricular haemorrhage. The patient underwent an urgent ICH evacuation craniotomy. After the procedure, the patient was treated in the intensive care unit. The patient was intubated for 4 days. Then, on the fifth day of stay in the ICU, a tracheostomy was performed on the patient. Conclusion: Spontaneous ICH has high mortality and morbidity. ICH management is mainly on timely targeted blood pressure management, effective and rapid reversal of coagulopathy to prevent hematoma expansion, and uncompromising intracranial pressure management.